Identity Crisis in the Hero’s Journey of Ruby Gillman; Teenage Kraken (2023) - Anisa Nurhidayanti; Yuyun Nurulaen; Dian Nurrachman (Universitas Islam Negeri Palopo, 2026)
This study analyzes the 2023 DreamWorks animated film Ruby Gillman, Teenage Kraken to explore how the protagonist's growth reflects psychological maturation amid internal conflicts and social pressures. Using a qualitative narrative approach, this research combines the hero's journey with Erik Erikson's psychosocial theory, offering a novel interdisciplinary framework that maps mythic archetypes onto adolescent identity formation. This integration contributes to film and literary studies by demonstrating how commercial animated cinema utilizes classical narrative structures to articulate complex psychological crises. In conclusion, this research demonstrates that each phase of the monomyth serves as a precise metaphor for the Identity vs. Role Confusion crisis. By transitioning from a passive Identity Foreclosure through a vulnerable Psychosocial Moratorium, the protagonist successfully attains Identity Achievement and the virtue of Fidelity. Ultimately, this contemporary animation redefines true maturation not as social conformity, but as the ego's courage to embrace a hybrid self to achieve a stable sense of self-sameness.